Effects of Organic and Inorganic Fertilizers on the Growth of NH-Ae 47-4 Variety of Okra - Molik A Zainab; Eluwa C Vincent; Oluwatobi S Ayodele; Gayus Y Lakwannum; Olorunmaiye S Kehinde (Journal of Applied Sciences and Environmental Management)
The paper evaluates the effects of organic and inorganic fertilizers on the growth of okra (variety NH-Ae  47-4. Organic fertilizers (cow dung and poultry droppings) and inorganic (NPK 15:15:15 and Urea 64:0) fertilizers were used for the experiment. The fertilizers were weighed and applied at 5g, 10g and 15g and were replicated three times and each having a control. Vegetative growth parameters taken include, shoot fresh weight (g), dry weight (g), plant height (cm), leaf number, stem girth (cm), leaf area (cm2). The results obtained from the experiment showed that the effect of the treatments were significantly difference from the control for all the parameters accessed with urea fertilizer having least effect. Plants treated with poultry litters have best performance by recording the highest fresh and dry weight (0.39g) at 4 weeks after planting (WAP); highest stem height 29.33cm for all the concentrations applied. Similarly, it has highest leaf area and stem girth (64.67cm2and 2.23cm respectively) at 8WAP. ©JASEM